School performance in youth after a concussion - DeMatteo, Carol A.; Jakubowski, Josephine; Randall, Sarah; Stazyk, Kathy; Lin, Chia-Yu; Yakubov, Rebecca (Frontiers in Sports and Active Living, 2022)
Objective: This study aimed to identify school problems and level of cognitive activity in youth aged 5-18 years with concussion during recovery stages of Return to School (RTS). Study Design: In a prospective cohort, participants completed in-person assessments at 3 time points with the post-concussion symptom scale (PCSS), and a cognitive activity scale, being completed every 48 hours until symptom-resolution was achieved. Participants and their parents completed a school questionnaire detailing how their concussion had impacted their school learning/performance and their level of concern about their injury as well as the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT). Results: Sixty-three percent (N=44/70) of participants returned to school by the First visit post injury (average 7.7 days following injury) and of these 50% (N=22) were experiencing school problems. Sixty-five participants returned to school at the Follow-Up visit, and of these, 18% reported school problems. There was a significant difference in the school problems reported by parents and youth, at the First visit post injury(p=0.02) and the In-Person Symptom Resolution visit(p=0.00). The cognitive activity score increased, while the PCSS score decreased, from RTS Stage 1 to Stage 5. Conclusions: This study identified that 50% of youth experienced school problems at the First visit post injury, whereas only 18% reported school problems at the Follow-Up visit. There is a significant difference in the perception of school problems reported by youth and their parents at different stages of recovery. Amount and complexity of cognitive activity increased with decreasing symptoms and increasing RTS Stage.